KEDUDUKAN PERUSAHAAN MULTINASIONAL SEBAGAI SUBJEK HUKUM INTERNASIONAL - Halima, Nazla Haditya; Muhammad, Danang Wahyu (Legal Standing : Jurnal Ilmu Hukum, 2024)
This article aims to analyze the position of multinational corporations as subjects of national law and international law and to analyze the imposition of responsibilities on multinational corporations in unlawful acts. The research method used in this paper is normative juridical by using laws and concepts. Indonesian national law does not specifically regulate national corporate entities. However, it is described through Law Number 40 of 2007 concerning limited liability companies. Whereas in international law multinational companies have been accommodated in various international agreements and conventions as well as international principles. Specific national laws do not regulate multinational corporations. However, it is quite possible to achieve harmony between multinational corporations and states as entities governed by international law. However, Law Number 40 of 2007 concerning Limited Liability Companies (UUPT of 2007) stipulates that the direction is responsible for the management. This is because of the important role and strategic direction as the management of a limited liability company. Meanwhile, the board of commissioners is responsible for overseeing company management policies according to regulations, advising directors on how to manage the company, and approving or assisting directions to take certain actions in terms of equity and business management in emergencies.